IMPORTANCE OF TRANSPORT NETWORKS IN THE ECONOMY OF SURKHANDARYA REGION - Kholmamat Jurayevich Khidirov (Scholar Express Journal, 2021)
The article discusses the role of water and air transport in the transport system of the Surkhandarya oasis. In particular, it is necessary to emphasize the importance of water transport in the development of the national economy. This type of transport is cheap and convenient, and can deliver a large amount of cargo to the desired destination. In addition, water transport plays an important role in the development of the country. If we look at the most developed countries on earth, we can see that they are all located on large rivers that allow access to the sea or the world's oceans.
Keywords: Vakhandaryo; Pamirdaryo; Gunt; Korasuv river; Koraqum; Kizilkum Araks